Availability of fluoride from meals given to kindergarten children in Brazil - Buzalaf MAR, Pinto CS, Rodrigues MHC, Levy FM, Borges AS, Furlani TA, (Blackwell Synergy, 2006)
The aim of this study was to evaluate the amount of fluoride supplied daily in the meals given in 44 public kindergarten schools in Bauru, Brazil